1998
DOI: 10.1038/sj.ejhg.5200234
|View full text |Cite
|
Sign up to set email alerts
|

Detailed mapping of the phosphomannomutase 2 (PMM2) gene and mutation detection enable improved analysis for Scandinavian CDG type I families

Abstract: The gene for carbohydrate-deficient glycoprotein syndrome type I (CDG1) has previously been localised by us close to marker D16S406 in chromosome region 16p13.2-3. We also presented data indicating a strong founder mutation associated with a specific haplotype in CDG I patients from western Scandinavia. The phosphomannomutase 2 (PMM2) gene was recently put forward as a likely CDG1 candidate gene. We have now shown that the specific haplotype is associated with the PMM2 mutation 357C > A. Using data from radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 11 publications
1
42
0
1
Order By: Relevance
“…The entire group was also analysed for the presence of the second most frequent mutation, F119L, which is particularly prevalent in Scandinavia. 5,6,12 No carriers were identified in either set, indicating a much lower frequency of this mutation. On the basis of the disease frequency and allele distribution (see below), an estimated 1/500 to 1/1000 was expected.…”
Section: Frequency Of R141h In Two Normal Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The entire group was also analysed for the presence of the second most frequent mutation, F119L, which is particularly prevalent in Scandinavia. 5,6,12 No carriers were identified in either set, indicating a much lower frequency of this mutation. On the basis of the disease frequency and allele distribution (see below), an estimated 1/500 to 1/1000 was expected.…”
Section: Frequency Of R141h In Two Normal Populationsmentioning
confidence: 99%
“…4,8 The most intriguing observation is the total lack of patients homozygous for the most frequent mutation, R141H, present in more than 75% of patients of Caucasian origin. 4,5 On the other hand, patients homozygous for the other relatively frequent mutation, F119L, have been found, 4,6,9 (see also M Schwartz 1999, unpublished data) as well as one patient homozygous for the rare D65Y mutation. 4 These observations suggested that the R141H mutation is a severe mutation, and that homozygosity may not be compatible with life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] All but one of the 30 different mutations detected so far have been of the missense type. [2][3][4][5][6] Whilst most patients are compound heterozygotes, homozygosity for the F119L mutation has been observed in a few instances, and one patient is known to be homozygous for D65Y. 3,5,7 In contrast, patients homozygous for the R141H mutation, present in more than 75% of patients of Caucasian origin, have been conspicuously absent in results of the genotype analyses.…”
Section: Introductionmentioning
confidence: 98%
“…[2][3][4][5][6] Whilst most patients are compound heterozygotes, homozygosity for the F119L mutation has been observed in a few instances, and one patient is known to be homozygous for D65Y. 3,5,7 In contrast, patients homozygous for the R141H mutation, present in more than 75% of patients of Caucasian origin, have been conspicuously absent in results of the genotype analyses. 3,4 These observations suggest that homozygosity for R141H may not be compatible with life.…”
Section: Introductionmentioning
confidence: 98%